C-REACTIVE PROTEIN - THE MOST USEFUL REACTANT OF ACUTE PHASE IN RHEUMATOID ARTHRITIS - Spasovski, Dejan; Sandevska, Emilija; Jakupi, Ljindita Djemaili; Vaslievska, Ana; Balkanov, Svetlana Krstevska; Veljanovska, Aleksandra Pivkova; Jakimovska, Maja; Mitreski, Vladimir; Chamurovski, Nikola; Iseini, Kujtim (Journal of Morphological Sciences; Vol 6 No 1 (2023): JMS, 2023)
The aim of the study was to determine the most useful biochemical marker of the acute phase reactants for the evaluation of disease activity in rheumatoid arthritis (RA). Sixty patients with RA were included, 27 of whom were treated with non-steroid anti-inflammatory drugs (NSAIDs) and methotrexate (MTH). The control group consisted of 33 patients treated only with NSAIDs due to irregular control. In the first group, disease activity was evaluated at four-week intervals and in the control group at three- week intervals, following the scores of the articular indices, complete blood count (CBC), elevated sedimentation rate (ESR), and C-reactive protein (CRP) in every patient. In the first group of patients, decreased activity of RA was found in every subsequent control, with a consecutive decrease in the mean values of the scores of the articular indices and statistically significant differences in the four-time intervals. Considering laboratory parameters, there were statistically significant differences in the mean values of haemoglobin (Hb), erythrocytes (Er), platelets (Plt), and ESR (p=0.0462, p=0.0076, p= 0.0058, p= 0.0003). The mean values of CRP did not show statistically significant differences, but the number of patients who were CRP negative increased (the standard deviation also increased). In the group of patients treated only with NSAIDs, there were statistically significant differences in the mean values of the scores of the articular indices, with increases in every subsequent control (in favor ofdisease progression). There were no statistically significant differences considering CBC, ESR, and CRP (in favor of a permanently active disease). CRP is the most useful marker in the prospective evaluation of patients with rheumatoid arthritis. Keywords : rheumatoid arthritis, articular indices, reactants of the acute phase. https://doi.org/10.55302/JMS2361068s